Effects of energy extensivity on the quantum phases of long-range interacting systems - Botzung, Thomas; Hagenmüller, D.; Masella, G.; Dubail, J.; Defenu, Nicolò; Trombettoni, Andrea; Pupillo, G. (Physical review, 2021)
We investigate the ground state properties of one-dimensional hard-core bosons interacting via a variable long-range potential using the density matrix renormalization group. We show that restoring energy extensivity in the system, which is done by rescaling the interaction potential with a suitable size-dependent factor known as Kac's prescription, has a profound influence on the low-energy properties in the thermodynamic limit. While an insulating phase is found in the absence of Kac's rescaling, the latter leads to a new metallic phase that does not fall into the conventional Luttinger liquid paradigm. We discuss a scheme for the observation of this new phase using cavity-mediated long-range interactions with cold atoms. Our findings raise fundamental questions on how to study the thermodynamics of long-range interacting quantum systems.